Faith in the search of understanding - Surzyn, Jacek (Folia Philosophica, 2011)
Review of Luigi Iammarrone's book Giovanni Duns Scotus: Metaphysician and Theologian. The Fundamental Themes of His Philosophy and Theology. 1st edition. Rome: Miscellanea Francescana, 1999; 2nd edition. Rome: Miscellanea Francescana, 2003.